2016
DOI: 10.1101/gad.275891.115
|View full text |Cite
|
Sign up to set email alerts
|

An African-specific polymorphism in the TP53 gene impairs p53 tumor suppressor function in a mouse model

Abstract: A nonsynonymous single-nucleotide polymorphism at codon 47 in TP53 exists in African-descent populations (P47S, rs1800371; referred to here as S47). Here we report that, in human cell lines and a mouse model, the S47 variant exhibits a modest decrease in apoptosis in response to most genotoxic stresses compared with wild-type p53 but exhibits a significant defect in cell death induced by cisplatin. We show that, compared with wild-type p53, S47 has nearly indistinguishable transcriptional function but shows im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
307
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(327 citation statements)
references
References 40 publications
5
307
4
Order By: Relevance
“…Using Ingenuity pathway analysis, we found a hypothetical connection between PHKG2 and iron metabolism involving p53 (Fig. S3), which has itself been linked to ferroptosis regulation (48,49), providing an avenue for future exploration. Because we know that decreased iron levels suppress erastin lethality (6), this iron regulatory function of PHKG2 is likely responsible for modulating sensitivity to erastin.…”
Section: Phkg2 Regulates Ferroptosis Through Modulation Of Availablementioning
confidence: 99%
“…Using Ingenuity pathway analysis, we found a hypothetical connection between PHKG2 and iron metabolism involving p53 (Fig. S3), which has itself been linked to ferroptosis regulation (48,49), providing an avenue for future exploration. Because we know that decreased iron levels suppress erastin lethality (6), this iron regulatory function of PHKG2 is likely responsible for modulating sensitivity to erastin.…”
Section: Phkg2 Regulates Ferroptosis Through Modulation Of Availablementioning
confidence: 99%
“…Transcriptionally, this variant showed impaired ability to repress SLC7A11 or transactivate GLS2. Indeed, both human and murine cells containing this variant were markedly defective at inducing ferroptosis, and silencing of GLS2 essentially phenocopied this defect in cells with wild-type p53 (19). At this point, the search was on for an elucidation of the pathway whereby p53 regulates ferroptosis.…”
Section: Ferroptosis a New Pathway For P53-mediated Tumor Suppressionmentioning
confidence: 99%
“…Thus, it was unexpected when several different laboratories using in vivo mouse models demonstrated that these apoptotic and cell cycle effects of p53 were not needed for tumor suppression (10)(11)(12). More recently, it has been shown that another p53-mediated response, ferroptosis, may be a key player in tumor suppression (13,14). The current study by Bublik et al (1) adds another possible role for wild-type p53 in preventing cancer development, namely negatively regulating FGF13 expression and its effects on ribosomal RNA synthesis in the nucleolus.…”
mentioning
confidence: 99%